Ratchet current and scaling properties in a nontwist mapping - Rolim Sales, Matheus [UNESP]; Borin, Daniel [UNESP]; de Souza, Leonardo Costa; Szezech, José Danilo; Viana, Ricardo Luiz; Caldas, Iberê Luiz; Leonel, Edson Denis [UNESP] (Elsevier, 2024)
We investigate the transport of particles in the chaotic component of phase space for a two-dimensional, area-preserving nontwist map. The survival probability for particles within the chaotic sea is described by an exponential decay for regions in phase space predominantly chaotic and it is scaling invariant in this case. Alternatively, when considering mixed chaotic and regular regions, there is a deviation from the exponential decay, characterized by a power law tail for long times, a signature of the stickiness effect. Furthermore, due to the asymmetry of the chaotic component of phase space with respect to the line I=0, there is an unbalanced stickiness that generates a ratchet current in phase space. Finally, we perform a phenomenological description of the diffusion of chaotic particles by identifying three scaling hypotheses, and obtaining the critical exponents via extensive numerical simulations.
Keywords: Critical exponents; Ratchet effect; Scaling invariance; Unbalanced stickiness